Laser‐Directed Assembly of Nanorods of 2D Materials. Issue 46 (2nd October 2019) - Ibrahim, Khaled; Novodchuk, Inna; Mistry, Kissan; Singh, Michael; Ling, Christopher; Sanderson, Joseph; Bajcsy, Michal; Yavuz, Mustafa; Musselman, Kevin P.
Abstract: Herein, the previously unrealized ability to grow nanorods and nanotubes of 2D materials using femtosecond laser irradiation is demonstrated. In as short as 20 min, nanorods of tungsten disulfide, molybdenum disulfide, graphene, and boron nitride are grown in solutions. The technique fragments nanoparticles of the 2D materials from bulk flakes and leverages molecular scale alignment by nonresonant intense laser pulses to direct their assembly into nanorods up to several micrometers in length. The laser treatment process is found to induce phase transformations in some of the materials, and also results in the modification of the nanorods with functional groups from the solvent atoms. Notably, the WS2 nanoparticles, which are ablated from semiconducting 2H WS2 crystallographic phase flakes, reassemble into nanorods consisting of the 1T metallic phase. Due to this transition, and the 1D nature of the fabricated nanorods, the WS2 nanorods display substantial improvements in electrical conductivity and optical transparency when employed as transparent conductors. Abstract : A new technique to grow nanorods of 2D materials using femtosecond laser treatment is introduced. Nanorods of graphene, molybdenum disulfide, tungsten disulfide, and boron nitride several micrometers long are fabricated in as short as 20 min via Coulomb explosion and molecular scale alignment of nanoparticles by nonresonant intense laser pulses.